Why the Catholic Church Is So Conflicted about Sex. - KOHANSKI, DANIEL (Humanist)
The article discusses the sex abuse scandals involving Catholic clergy and the Church's obsession for controlling people's sexual behavior since the inception of Christianity. It notes that it relates to Middle Eastern civilization and the Hittite Empire of the second millennium BCE, with the Hittites having always believed that sex made a person ritually unclean. It adds that Augustine considered sex as sin after becoming the Bishop of Hippo.